Coprophilous fungi in Africa: documented species and their distribution - Njouonkou, André-Ledoux; Mouanfon, Zouberou Njiaghait; Aïgnon, Hippolite Lougbégnon; Tchamgoue, Joseph; Teponno, Rémy Bertrand; Mapongmetsem, Pierre Marie; Yorou, Nourou Soulemane; Kouam, Simeon Fogue (Phytotaxa, 2025)
Fungi grow on a wide range of substrates, including animal dung, particularly that of herbivorous. Those thriving on dung are saprotrophs and called coprophilous. Africa, with its diversity of ecosystems, fauna, and flora, potentially has a rich and diverse coprophilous biota. Despite efforts to study them, they remain poorly documented, with patchy publications. This review aimed to survey the literature on coprophilous fungi and fungus-like organisms in Africa, produce a preliminary checklist, and outline the types of animal dung where they have been collected. Sixty-two scientific papers mentioned coprophilous fungi in Africa, with North and East Africa leading, while West Africa has the lowest. In total, 530 valid species are documented, with their taxonomic position updated according to Index Fungorum, MycoBank, and recent volumes of Outline of Fungi and fungus-like taxa. The documented species are distributed in Ascomycota (78%), Basidiomycota (9%), Mucoromycota (7%), fungus-like protists Myxomycota (5%), and Zoopagomycota (1%). The Sardariomycetes, Agaricomycetes, and Mucoromycetes are the most documented classes in Ascomycota, Basidiomycota, and Mucoromycota, respectively, while Pezizales, Agaricales, and Mucorales are the most documented orders in their phylum. Ascobolus immersus is documented in all regions of Africa. The Bovidae dung has the highest number of documented species, followed by Equidae’s and Elephantidae’s. Most species are documented from a single type of dung family. The most indifferent species include Sporormiella minima, Sordaria tomento-alba, Zygopleurage zygospora and Sordaria macrocarpa. This review highlights the significant gap in our knowledge of the documented coprophilous fungi in Africa and underscores the need to support the implementation of fundamental and applied research on this group on the continent.